Therapeutic effects of KRM-II-81, positive allosteric modulator for α2/3 subunit containing GABAA receptors, in a mouse model of Dravet syndrome - Sachiko Nakakubo; Yasuyoshi Hiramatsu; Takeru Goto; Syuhei Kimura; Masashi Narugami; Midori Nakajima; Yuki Ueda; Hideaki Shiraishi; Atsushi Manabe; Dishary Sharmin; James M. Cook; Kiyoshi Egawa (Frontiers Media S.A., 2023)
Introduction: Dravet syndrome (DS) is an intractable epilepsy syndrome concomitant with neurodevelopmental disorder that begins in infancy. DS is dominantly caused by mutations in the SCN1A gene, which encodes the α subunit of a voltage-gated Na channel. Pre-synaptic inhibitory dysfunction is regarded as the pathophysiological mechanism, but an effective strategy for ameliorating seizures and behavioral problems is still under development. Here, we evaluated the effects of KRM-II-81, a newly developed positive allosteric modulator for α 2/3 subunit containing GABAA receptors (α2/3-GABAAR) in a mice model of DS both in vivo and at the neuronal level.Methods: We used knock-in mice carrying a heterozygous, clinically relevant SCN1A mutation (background strain: C57BL/6 J) as a model of the DS (Scn1aWT/A1783V mice), knock-in mouse strain carrying a heterozygous, clinically relevant SCN1A mutation (A1783V). Seizure threshold and locomotor activity was evaluated by using the hyperthermia-induced seizure paradigm and open filed test, respectively. Anxiety-like behavior was assessed by avoidance of the center region in locomotor activity. We estimated a sedative effect by the total distance traveled in locomotor activity and grip strength. Inhibitory post synaptic currents (IPSCs) were recorded from a hippocampal CA1 pyramidal neuron in an acutely prepared brain slice.Results: KRM-II-81 significantly increased the seizure threshold of Scn1aWT/A1783V mice in a dose-dependent manner. A low dose of KRM-II-81 specifically improved anxiety-like behavior of Scn1aWT/A1783V mice. A sedative effect was induced by relatively high dose of KRM-II-81 in Scn1aWT/A1783V mice, the dose of which was not sedative for WT mice. KRM-II-81 potentiated IPSCs by increasing its decay time kinetics. This effect was more prominent in Scn1aWT/A1783V mice.Discussion: Higher activation of α2/3-GABAAR by KRM-II-81 suggests a compensatory modification of post synaptic inhibitory function against presynaptic inhibitory dysfunction in Scn1aWT/A1783V. The increased sensitivity for KRM-II-81 may be relevant to the distinct dose-dependent effect in each paradigm of Scn1aWT/A1783V mice.Conclusion: Selective activation for α2/3-GABAAR by KRM-II-81 could be potential therapeutic strategy for treating seizures and behavioral problems in DS.